Vaccination of pregnant rhesus monkeys with inactivated rotavirus as a model for achieving protection from rotavirus SA11 infection in the offspring. Issue 12 (2nd December 2021) - Yin, Na; Wu, Jinyuan; Kuang, Xiangjing; Lin, Xiaochen; Zhou, Yan; Yi, Shan; Hu, Xiaoqing; Chen, Rong; Liu, Yaling; Ye, Jun; He, Zhanlong; Sun, Maosheng; et al.
ABSTRACT: Live-attenuated rotavirus vaccine has shown low protection in underdeveloped or developing countries. However, the inactivated rotavirus vaccine may have the potential to overcome some of these challenges. In the present study, the immunogenicity and protective efficacy of a bivalent inactivated rotavirus vaccine by parenteral administration were elevated in a neonatal rhesus monkey model. A bivalent inactivated rotavirus vaccine containing G1P[8] (ZTR-68 strain) and G9P[8] (ZTR-18 strain) was administered to pregnant rhesus monkeys twice at an interval of 14 days. Neutralizing antibodies against RV strains ZTR-68, ZTR-18, SA11, WA, UK, and Gottfried emerged in pregnant rhesus monkeys and were transplacentally transmitted to the offspring. In the vaccine group, clinical symptoms of diarrhea, viral load in the gut tissue and histopathological changes were significantly reduced in the neonatal rhesus monkeys following oral challenge with the SA11 strain.